Religiusitas dalam Kumpulan Puisi Rekah Lembah Karya Mudji Sutrisno - Laura Andri R.M (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2019)
Poetry is not only seen from the structure. More than that, poetry is one of the means to convey messages to the public. This study examines the meaning of religiosity of the poems collection of Rekah Lembah by Mudji Sutrisno. The poems in the book have religious themes or are related to divinity and faith. Therefore, research is carried out with a review of themes to determine aspects of religiosity. The method used is descriptive qualitative method. So that finally an interpretation can be found that will produce interpretations in understanding the religious meaning as a whole.The meaning of religiosity contained in the collection of Rekah Lembah poetry by Mudji Sutrisno is: (1) religiosity between humans and God; (2) religiosity among fellow humans; and (4) human religiosity with him.